The securitization of aliens’ integration in France (Academic Journal of Internal Affairs, 2020)
The securitization of integration is an extremely complex process, as the host state must take into account its own functioning, the needs and specialities of those willing to be integrated. We also must take into consideration the fact that immigrants are not only passive participants in the integration process, but also actively respond to both prejudices and attitudes towards them. That is why special attention must be paid to ensure that the securitization of integration does not miss the goal, i.e. does not have the opposite effect. Due to historical and geographical aspects, migration and thus integration issues playa key role in France, as the proportion of immigrants in the country as a whole is still at about 9%.
Keywords: integration; migration; securitization; France